2021
DOI: 10.3390/educsci11050248
|View full text |Cite
|
Sign up to set email alerts
|

A Survey Study on U.S. College Students’ Learning Experience in COVID-19

Abstract: COVID-19 affected various aspects of our life. Many college students were forced to take courses remotely. It was not clear how they adapted to this new environment and how their mental health was affected. The objective of this study is to understand college students’ learning experience one year after the outbreak of COVID-19. An online survey was developed to investigate students’ overall learning process, mental health, perception of the learning community and student support. Sixty-two college students in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 22 publications
2
30
0
3
Order By: Relevance
“…Conversely, Quintiliani et al [46] found difficulties related with adapting to the new situation, maintaining attention during class, performing evaluations, coping with increased stress, and worrying about academic performance. Zhou and Zhang [47] mentioned the importance of students' mental health in the learning process and found the main obstacle to this during the lockdown to have been the lack of interaction with teachers and fellow students. Apolloni et al [48] highlighted good communication in online education as a protective factor generating resilience in situations of confinement.…”
Section: Resilience and Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, Quintiliani et al [46] found difficulties related with adapting to the new situation, maintaining attention during class, performing evaluations, coping with increased stress, and worrying about academic performance. Zhou and Zhang [47] mentioned the importance of students' mental health in the learning process and found the main obstacle to this during the lockdown to have been the lack of interaction with teachers and fellow students. Apolloni et al [48] highlighted good communication in online education as a protective factor generating resilience in situations of confinement.…”
Section: Resilience and Educationmentioning
confidence: 99%
“…Similarly, Eva et al [49] found that students who were able to regulate their emotions during the confinement obtained greater personal satisfaction and better academic results. As for Zhou and Zhang [47], they found the greatest problem facing students during the lockdown was the lack of personal relations with teachers and fellow students, while Ferreira et al [57] highlighted the importance of family and neighbours as resilience-promoting factors during the confinement. These studies are in line with Yu and Yu [58], who report significant differences in how students deal with emotional problems depending on their sex and academic degree.…”
Section: Resilience and Covidmentioning
confidence: 99%
“…Several case studies were conducted [18][19][20] but these, too, focused on specific departments or modules within a university. Both qualitative [21,22] and quantitative research [8,[23][24][25][26] was conducted, both in developing [27][28][29][30], and developed countries [31][32][33] as well as in post-communist countries [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Part of these perceptions and relationships are already described in very recent literature regarding academic adjustment in the pandemic [48][49][50][51][52][53]. Still, one should notice that this is a very new research field, with a lot of space for investigation.…”
Section: Introductionmentioning
confidence: 85%